ASSESSMENT OF SOIL PROPERTIES UNDER TEAK PLANTATATION IN ABIA - BADAGRY, LAGOS, NIGERIA - Ayo Omotayo; Ogundele, F.O (Indonesian Journal of Geography, 2013)
This paper investigated whether the Teakplantation established a year ago by Lagos State Government Ministry of Agric and Co-operative at Abia-Badagry meet the soil and environmental requirement as obtainable in countries where Teak grows naturally. Also the study will also establish whether the establishment of Teak tree has changed the soil properties. Sampling design for this study was based on, the need to spread sample sites objectively over the study area. The entire plantation is 2.5ha and five soil samples were collected from the plantation using soil auger. From each of thefive (5) holes dug, soil samples were randomly collected from two sampling depths 0 - 15 em and 15-30cm, respectively. Soil samples were air-dried, sieved, 'and analyzed in the laboratory using standard techniques. The result of the soil analysis show that PH, EC, TOM, TOC, TN, Av.K, Av.P and Bulk Density ranges between,5.36-5.86,38.00-156.00,1.06-2.41,0.86- 1.92,0.01-0.03,0.03-0.03,0.02-0.02 and 1.31-1.36 respectively. Among the examined variables,Ec has the highest mean (61.00) followed by pH (5.72) while TN/Av.P remained the least value (0.02). Also, EC recorded the highest Standard Deviation (46.73).this was followed by TOM (0.52) while Av.K/Av. Based on the empirical data and the analysis carried out on the Teak plantation and the site characteristics tofind out the suitability or otherwise of the site for maximum Teak yield in the country, it was found that the site characteristics, especially, soil properties are similar to those'of places where Teak grows naturally. Therefore it is recommended to Lagos State Ministry of Agric and Cooperative to increase the plantation size.